Interrelationships and zoning-based management of landscape ecological risk and ecological resilience in the Hefei metropolitan circle from a multi-scale perspective - Liu, Junhao; Li, Jiulin; Wang, Yingxing (Frontiers in Environmental Science, 2025)
Assessing the ecosystem resilience and risks of metropolitan areas helps coordinate ecological environmental protection, reduce landscape ecological risks, and enhance ecological resilience. Existing studies often analyze the trade-offs and synergies between landscape ecological risks and ecological resilience within specific regions based on administrative divisions. However, the mechanisms underlying these trade-offs and synergies across different scales remain unclear. This study focuses on the Hefei Metropolitan Area in China, constructing quantitative assessment models for ecological resilience and landscape ecological risks from a landscape pattern perspective. It systematically examines the spatiotemporal evolution characteristics of these two aspects from 2010 to 2020 across multiple scales, including grid, county, and city levels. Pearson correlation analysis and bivariate spatial autocorrelation are employed to investigate their spatial interactions. Furthermore, a coupling coordination model is used to identify trade-offs and synergies between the two at different scales. Finally, based on the interaction analysis, tailored zoning regulation strategies are proposed. Key findings reveal: (1) Over the past decade, the landscape ecological risk in the Hefei Metropolitan Circle has exhibited characteristics of “stable overall pattern with localized differentiation,” where high-risk zones are predominantly concentrated in areas with elevated water body ratios. Ecological resilience exhibited a slight declining trend, with an overall low resilience level. High-resilience zones experienced a significant reduction of 50.6% in area, while low-resilience zones expanded toward the core urbanization areas. (2) A robust negative correlation emerged between ecological resilience and landscape risk, intensifying significantly with finer spatial scales. Crucially, the recoverability dimension exerted the most potent counteracting effect on risk propagation. (3) The mean coupling coordination degree between ecological resilience and ecological risk across multiple scales registered below 0.5, with spatial heterogeneity manifesting as “higher in the southwest and generally low in other areas.” Coordination zones are sporadically distributed within southwest woodlands, while dysregulation zones concentrate predominantly in water bodies and urbanization-intensive belts. (4) Collectively, low-resilience/high-risk zones clustered in waterbody-dense areas, contrasting with high-resilience/low-risk clusters predominantly occupying forested biomes. This spatial divergence exhibited scale-dependent amplification under finer resolutions. Synthesizing multiscale correlations and coupling coordination patterns, we delineate a four-type governance typology. This study provides both theoretical underpinnings and practical pathways for multi-scale collaborative governance to enhance regional ecological resilience and advance sustainable development.